Math, asked by agrima48, 1 year ago

solve any question.i'll be greatful.​

Attachments:

Answers

Answered by sonalithakur82
2

Answer:

hi there here is the answer to u r question.......

Step-by-step explanation:

19 i)  2x^4-6x^3+3x^2+3x-2 / x^2 -3x+2

so

x^2-3x+2  )    2x^4-6x^3 +3x^2+3x-2  (   2x^2-1

                     2x^4-6x^2+4x^2

                   -------------------------------------

                                        -x^2+3x-2

                                       -x^2+3x-2

                         ---------------------------------------

                                           0

ii)x^2-3x+2=0

  x^2-2x-x+2=0

   x(x-2)-1(x-2)

   (x-1)(x-2)

x= 1 or 2

case 1 :

when p(1) =2 *1^4-6*1^3+3*1^2+3*1-2

                =2-6+3+3-2

              =0

so remainder is 0 so it divedes the polynomial completely

when p(2)=2 *2^4-6*2^3+3*2^2+3*2-2

                  2*16-6*8+12+6-2

               = 32-48+18-2

               =50-48-2

              =50-50

              =0

so remainder is 0 so it divedes the polynomial completely.

                                                                       

Similar questions